1998
DOI: 10.1111/j.1574-6968.1998.tb13232.x
|View full text |Cite
|
Sign up to set email alerts
|

A plasmid that encodes three genes for resistance to macrolide antibiotics inStaphylococcus aureus

Abstract: In previous letters, FEMS Microbiol. Lett. 148 (1997) 91-96, it was demonstrated that plasmid pMS97-obtained from a in 1971 clinically isolated Staphylococcus aureus strain MS8968 resistant to macrolide (Mac) antibiotics--carried an msrA gene and uncharacterized erm gene, respectively. msrA encodes a cytoplasmic membrane protein that mediates the so-called 'active Mac-efflux' (designated hereafter as msrSA') and erm encodes a methyltransferase by which a specific adenine residue of 23S rRNA is modified: methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…These resistance mechanisms have not been considered of major clinical importance because enterobacteria are not targets for macrolides. Some clinical isolates of S. aureus produce phosphotransferases, but this event remains rare [ 72 74 ]. In pathogenic microorganisms, the impact of the three mechanisms is unequal in terms of incidence and clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…These resistance mechanisms have not been considered of major clinical importance because enterobacteria are not targets for macrolides. Some clinical isolates of S. aureus produce phosphotransferases, but this event remains rare [ 72 74 ]. In pathogenic microorganisms, the impact of the three mechanisms is unequal in terms of incidence and clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Different research groups have recognized a number of enzymatic inactivation processes, which involve the most important antibiotic classes. These chemical transformations comprise hydrolysis, group transfer, and redox (mainly oxidation) reactions [ 29 , 30 , 31 , 32 ].…”
Section: Mechanisms Of Resistance and Antibiotics From Actinomycetes : An Overviewmentioning
confidence: 99%
“…Following this discovery several more enzymes have been found that show a similar activity. These MPHs all mediate the transfer of the γ-phosphate group from GTP onto the macrolide substrates and doing so confer resistance to a group of bacteria ranging from Gram-negative ( E. coli, Pseudomonas, Pasteurella, Klebsiella, Serratia, Shigella ) to Gram-positive ( Staphylococcus ) ( Matsuoka et al, 1998 , 2003 ; Nguyen et al, 2009 ; Ferjani et al, 2012 ; Mendes et al, 2017 ).…”
Section: Macrolide Phosphotransferasesmentioning
confidence: 99%
“…At least 15 gene subtypes of MPHs have been reported, which are designated mph (A) to (O) ( O’Hara et al, 1989 ; Kono et al, 1992 ; Kim et al, 1996 ; Matsuoka et al, 1998 , 2003 ; Roberts et al, 1999 ; Schlüter et al, 2007 ; Pawlowski et al, 2016 , 2018a ). Here, we name their products MPH(2′)-I to MPH(2′)-XV, respectively, with the assumption that all these MPHs phosphorylate the hydroxyl on the C5 linked desosamine or mycaminose moiety, which is present in all macrolides and ketolides that bind to the 23S rRNA where it forms a critical interaction with A2058 (see Figure 2 ).…”
Section: Macrolide Phosphotransferasesmentioning
confidence: 99%